SURVEY TENTANG MODEL PEMBELAJARAN PENDIDIKAN JASMANI BERBASIS PEMBERIANMASALAH GERAK DI SEKOLAH MENENGAHPERTAMA DI KOTA BANDUNG - Uhamisastra Yusup Hidayat (Jurnal Pendidikan Jasmani Indonesia, 2006)
The purpose of this research is to find out the feasibility of physical education learningprocess which is based on movement problem based learning. A number of 70 physicaleducation teachers of Junior High School at Bandung municipality were chosen as samplesand asked to fill up inquiries on physical educational learning process based on movementproblem based learning. These 70 samples were chosen by purposive random samplingtechnique. The results of data tabulation by percentage technique indicate that the teachersphysical educational at Bandung has commonly used physical education learning modelwhich is based on movement problem based learning. According to this research it issuggested to arrange a continuation research which involves more samples and includesBase/Basic School and Senior High School. It is also strongly recommended to find anylearning model of Physical Educational based on movement problem based learningwhich is more appropriate with Indonesian culture.Keywords : Learning Models, Physical Education, Movement Problem Based Learning.